Evaluation of Tension at Median and Ulnar Nerve Repairs at the Wrist in a Cadaveric Model. (March 2021) - Usmani, Rashad H.; Rainville, Aundrea; Botkin, Deana; Merrell, Gregory A.
Background: Median and ulnar nerve lacerations at the wrist are often combined with zone 5 tendon injury. The inability to provide early range of motion leads to increased adhesions. Current therapy protocols recommend the wrist be held in 30° of flexion post operatively to protect the nerve repair. However, if tension and elongation across the nerve repair stay under a critical level in less wrist flexion, postoperative splinting in more extension could allow for better tendon excursion and less adhesions.Methods: Six cadaveric specimens were used. After appropriate dissection, the median and ulnar nerves were transected and repaired with a single 10-0 nylon suture. The wrist was ranged from 30° flexion to 45° extension to see if the repair would fail. Next, an epineural repair was accomplished with 9-0 nylon suture. The percent elongation along the nerve repair was measured at set increments from 30° flexion to 45° extension.Results: In all 6 specimens, median and ulnar nerve repairs with a single 10-0 nylon suture did not fail with wrist range of motion from 30° flexion to 45° extension. Mean percent elongation stayed under critical levels in up to 30° of extension.Conclusions: Both median and ulnar nerve repairs stayed under critical levels of tension and elongation in up to 30° of wrist extension. We believe it is possible to be more aggressive with wrist positioning in wrist level median and ulnar nerve repairs.